The modified Delphi method. An approach from the Soft Systems Methodology [El método delphi modificado. Un acercamiento desde la metodología de sistemas suaves] (2015)
The article presents a revision of a state of the art related to the Delphi method, its definitions, characteristics and applications. Based on this revision, its problems were identified, and one of them related to the non-structure structuring of problems of human activity was analyzed. With the end of complementing the analysis, a case of the application of soft system methodology was made, conceived in the 1960's by Peter Checkland in a Doctoral dissertation related to the Delphi method and its alignment with an innovation strategy in the frame of a management innovation model; with the purpose of generating a solved problem. Amongst the main conclusions, the advantages of the use of a soft system methodology were highlighted to help the improvement of non-structured human activity with the Delphi method, and its alignment with the company's innovation strategy in the frame of innovation management models. Also, the possibility of complementing the soft system methodology with priority surveys to obtain expert opinion related with the components of a Doctoral dissertation.